2020
DOI: 10.1002/cssc.202001605
|View full text |Cite
|
Sign up to set email alerts
|

The Oxygen Reduction Reaction in Ca2+‐Containing DMSO: Reaction Mechanism, Electrode Surface Characterization, and Redox Mediation**

Abstract: In this study we strengthen our fundamental understanding of the underlying reactions of a possible Ca-O2 battery using a DMSO based electrolyte. Employing the rotating ring disc electrode, we find a transition from a mixed process of O2and O2 2formation to an exclusive O2formation at gold electrodes. We will show that in this system Ca-superoxide and Ca-peroxide are formed as soluble species. However, there is a strongly adsorbed layer of ORR products on the electrode surface which is blocking the electrode. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(19 citation statements)
references
References 65 publications
0
19
0
Order By: Relevance
“…In the above chemical mixing experiment (Figure 3e), OER was observed together with the formation of CO, CO 2 , SO 2 , H 2 O and CH 2 O as detected by mass spectrometer, [29b] which indicates that the disproportionation reaction is accompanied by the formation of 1 O 2 . 1 O 2 was shown to originate from superoxide disproportionation and attack electrolyte to evolve parasitic gases [9c] .…”
Section: Current Status Of Mechanistic Understandingmentioning
confidence: 77%
See 2 more Smart Citations
“…In the above chemical mixing experiment (Figure 3e), OER was observed together with the formation of CO, CO 2 , SO 2 , H 2 O and CH 2 O as detected by mass spectrometer, [29b] which indicates that the disproportionation reaction is accompanied by the formation of 1 O 2 . 1 O 2 was shown to originate from superoxide disproportionation and attack electrolyte to evolve parasitic gases [9c] .…”
Section: Current Status Of Mechanistic Understandingmentioning
confidence: 77%
“…Reinsberg et al . reported using 2,5‐di‐tert‐butyl‐1,4‐benzoquinone (DBBQ) as a discharge mediator for Ca−O 2 batteries (Figure 3f) [29b] . The DBBQ mediator enhanced both ORR and OER currents.…”
Section: Current Status Of Mechanistic Understandingmentioning
confidence: 98%
See 1 more Smart Citation
“…The ORR mechanism on Au electrodes, which was described in detail in previous studies, is shown in Figure 8 for comparison. [23,24] In earlier studies on Au electrodes, [23,24] it was found that on a bare Au electrode in Ca(ClO 4 ) 2 containing DMSO, oxygen is reduced to peroxide, which dissolves into the bulk electrolyte. This peroxide can form a thick bulk layer on the electrode during continuous ORR, which slowly dissolves as no more peroxide is formed (as the potential is swept out of the ORR region).…”
Section: Mechanism Of Oxygen Reduction On Pt Electrodescomparison To Aumentioning
confidence: 99%
“…As soon as the adsorbate layer is complete, exclusively superoxide is formed on top of this adsorbate layer [23] . Instructive is the comparison to the Li case: the difference of the theoretical standard potentials for peroxide and superoxide formation (Δ E 0 ) is larger than 2 V for Ca 2+ , while Δ E 0 is smaller than 0.5 V for Li + [24] . Thus, Li ‐ superoxide is formed at gold electrodes prior to peroxide (for kinetic reasons), but in presence of Ca 2+ peroxide is directly formed in DMSO.…”
Section: Introductionmentioning
confidence: 99%